PENGARUH KOMPRES HANGAT JAHE MERAH (ZINGIBER OFFICINALE ROSCOE) TERHADAP PENURUNAN SKALA NYERI ARTRITIS REUMATOID PADA LANSIA DI UPT. PELAYANAN SOSIAL LANJUT USIA DAN ANAK BALITA WILAYAH BINJAI DAN MEDAN - Sunarti Sunarti (Universitas Prima Indonesia, 2018)
Rheumatoid arthritis is a musculoskeletal disease that is mostly experienced by elderly, which causes some complaints; such as, sore feet, knees, hips, hands, neck and various joints. Pain management is aimed at reducing the scale of the pain of rheumatoid arthritis in the elderly. Elderly have never been treated with red ginger warm compresses to reduce pain scale of rheumatoid arthritis. The aim of this study was to determine the effect of red ginger warm compress to decrease pain scale of rheumatoid arthritis in the elderly in UPT. Elderly Social Services and Early Childhood Regional Binjai and Medan in 2015. This type of research is pre experiment with the design of one group pre-post test design. The research was conducted in July 2015. The samples in this study were 20 elderly people who suffered from rheumatoid arthritis pain which were drawn by purposive sampling technique. Based on the results of this study, it is indicated that rheumatoid arthritis pain average scale before being treated with warm compress of ginger red (pre-test) was 3.60 with a standard deviation, 940. While the average scale of pain after the administration of the red ginger warm compresses (post-test) was 2.60 with a standard deviation, 940. Based on Wilcoxon statistical test, it was obtained that p-value of 0.000 (<0.05), meaning that there is significant effect of red ginger warm compress on the decrease of pain scale of rheumatoid arthritis in the elderly. The study concludes that there is an effect of red ginger warm compress on the decrease of pain scale of rheumatoid arthritis in the elderly and it can be used as an alternative therapy to reduce the scale of the pain of rheumatoid arthritis in the elderly.